The biological alterations of synapse/synapse formation in sepsis-associated encephalopathy - Tang, Chuan; Jin, Ye; Wang, Huan (Frontiers in Synaptic Neuroscience, 2022)
Sepsis associated encephalopathy (SAE) is a common complication caused by sepsis, and is responsible for increased mortality and poor outcomes in septic patients. Neurological dysfunction is one of the main manifestations of SAE patients. Patients may still have long term cognitive impairment after hospital discharge, and the underlying mechanism is still unclear. Here, we first outline the pathophysiological changes of SAE, including neuroinflammation, glial activation, and blood-brain barrier (BBB) breakdown. Synapse dysfunction is one of the main contributors leading to neurological impairment. Therefore, we summarized SAE induced synaptic dysfunction, such as synaptic plasticity inhibition, neurotransmitter imbalance, and synapses loss. Finally, we discuss the alterations in the synapse, synapse formation, and mediators associated with synapse formation during SAE. In this review, we focus on the changes in synapse/synapse formation caused by SAE, which can further understand the synaptic dysfunction associated with neurological impairment in SAE and provide important insights for exploring appropriate therapeutic targets of SAE.